2020
DOI: 10.1111/geb.13215
|View full text |Cite
|
Sign up to set email alerts
|

Niche dynamics in amphitropical desert disjunct plants: Seeking for ecological and species‐specific influences

Abstract: Aim Numerous studies have assessed whether species niches are conserved in geographically separated regions. However, most of them were performed on invasive species, with the limitation that such species have likely not yet reached their potential distribution in the invaded region. Here we test the hypothesis of niche conservatism in the entire group of 25 amphitropical desert disjunct plant species, naturally distributed in North and South America but absent in the tropics. We also assessed the influence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…Wasof et al (2015) concluded that the realized niches of disjunct arctic‐alpine plants in the Alps and Fennoscandia have largely been conserved since their population fragmentation after the LGM. In contrast, niches of desert plant species that are disjunctly distributed in North and South America were found to be at disequilibrium in terms of thermal preferences, which could have shifted to avoid competition at more productive sites (Quiroga et al 2021). In fact, HIM sites of R. hastatus are somewhat colder and exhibit a more continental climate than sites in the HDM (Miehe et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Wasof et al (2015) concluded that the realized niches of disjunct arctic‐alpine plants in the Alps and Fennoscandia have largely been conserved since their population fragmentation after the LGM. In contrast, niches of desert plant species that are disjunctly distributed in North and South America were found to be at disequilibrium in terms of thermal preferences, which could have shifted to avoid competition at more productive sites (Quiroga et al 2021). In fact, HIM sites of R. hastatus are somewhat colder and exhibit a more continental climate than sites in the HDM (Miehe et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Such shared disjunctions offer an unparalleled opportunity to reconstruct how geologic history has shaped the assembly of modern plant communities. More broadly, they also represent excellent systems for studying myriad fundamental processes in ecology and evolution, including speciation and diversification (Xiang et al, 2004; Yang et al, 2018), niche evolution (Wasof et al, 2015; Melton et al, 2022), biotic interactions (Quiroga et al, 2020), community assembly (Donoghue and Smith, 2004; Donoghue, 2008; Manos and Meireles, 2015; Dick and Pennington, 2019; Jiang et al, 2019), and evolutionary responses to climate change over both small and larger time scales (Qian and Ricklefs, 2004; Hamilton and Eckert, 2007; Kuhn et al, 2016).…”
Section: Figurementioning
confidence: 99%
“…However, due to technical limitations such as the application of SEM to data not fitting a Gaussian error distribution and the estimate of only linear relationships prevented a broader application of this methodology to data types commonly found in ecological studies (Grace, 2022; Lefcheck, 2016). Recent technical developments overcome some of these limitations (e.g., Carvalho‐Rocha et al., 2021; Cerqueira et al., 2021; Chu et al., 2019; Quiroga et al., 2021; Walentinowitz et al., 2023), but their application into SDMs remains surprisingly low.…”
Section: Incorporating Hypothesized Causal Relationships Into Sdmsmentioning
confidence: 99%